Co-producing an online patient public community research hub: a qualitative study exploring the perspectives of national institute for health research (NIHR) research champions in England - Eleanor Hoverd; Sophie Staniszewska; Jeremy Dale; Rachel Spencer; Anne Devrell; Dena Khan; Carrol Lamouline; Sanya Saleem; Pam Smith (Research Involvement and Engagement, 2024)
Abstract Background Patient and Public Involvement and Engagement (PPIE) should be embedded as part of researchers’ everyday practice. However, this can be challenging. Creating a digital presence for PPIE as part of Higher Education Institutes’ (HEIs) infrastructure may be one way of supporting this. This can support how information is made available to patients and members of the public, but relatively little is known about how HEIs can best do this. Our aim was to develop a university website for patients and members of the public to learn about ways to get actively involved in research and be able to access the results of health and social care research. Methods This project involved working as partners with five National Institute for Health and Care Research (NIHR) Research Champions. NIHR Research Champions are volunteers who raise awareness and share experiences about health and social care research. Content of a prototype Patient Public Community Research Hub website was co-produced with the Research Champions, and then 15 NIHR Research Champions from across England were asked for their views about the website. Findings The information collected told us that the Patient Public Community Research Hub was viewed as being beneficial for increasing visibility of PPIE opportunities and sharing the findings of studies though needs further work: to make the information more user-friendly; to improve the methods for directing people to the site and to create new ways of connecting with people. It provides a foundation for further co-development and evaluation. A set of recommendations has been developed that may be of benefit to other HEIs and organisations who are committed to working with patients and members of the public.